Workers' participation in Zimbabwe and Germany: lessons for Zimbabwe - Chipazi, Anthony Raymond (Centre for Law and Society, 2026)
This paper examines the concept of workers' participation in Zimbabwe (developing country) and Germany (developed country). Its main focus is on the institutional and social context of legislative framework in promoting workers' participation in the two countries. It is concerned with the practical operation of collective bargaining and other fonns of worker representation, the structure and functions of unions and employer associations, role of government agencies and the nature of political processes. Furthermore, it adds an international perspective to the concept of workers' participation through the lens of the International Labour Organisation (!LO). It also makes a comparative analysis of the functional equivalents between the different structures/institutions for workers' participation in Germany and Zimbabwe. By examining the German case, this provides insight into and lessons for Zimbabwe. While debate on workers' participation in Zimbabwe has mainly focused on the structure of present law, this paper argues that it is the application of law which reveals the true character of the institutions. It ends by suggesting a way forward on Zimbabwe's precipice with regard to workers' participation.